Pueraria montana var. lobata (Leguminosae) en la Argentina: estado actual de su naturalización - Delucchi, Gustavo (2014)
In this contribution, the current state of naturalization of Pueraria montana (Lour.) Merr. var. lobata (Willd.) Maesen & S. M. Almeida ex Sanjappa & Predeep (Leguminosae, Papilionoideae) in Argentina is discussed. This variety is considered invasive in Misiones province and naturalized in Buenos Aires province, based on floristic and ethnobotanical researches. A description of the variety, iconography, geographical distribution, reproductive biology, vernacular names, uses, expansion mechanisms, observations, and reference material are also presented.